Performance analysis of cooperative NOMA systems with adaptive mode selection and subchannel allocation - Cheng, Yanyu (2021)
In this paper, we study the mode selection and subchannel allocation for the downlink of a multi-user multi-subchannel cooperative non-orthogonal multiple access (C-NOMA) system. Specifically, each non-orthogonal multiple access (NOMA) pair can work in two different modes, i.e., non-cooperative NOMA (NC-NOMA) and C-NOMA, where the mode selection is based on the users' channel conditions. We propose an adaptive mode selection, subchannel allocation and user pairing (AMS-SAUP) scheme and derive the achievable diversity order by analyzing the upper bound for the outage probability. Simulation results reveal that the AMS-SAUP scheme achieves the same diversity order as the exhaustive search scheme.